2018
DOI: 10.1111/acem.13497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Screening Tool for Child Sex Trafficking Among Patients With High‐Risk Chief Complaints in a Pediatric Emergency Department

Abstract: ObjectivesThe objective was to apply and evaluate a screening tool to identify victims of child sex trafficking (CST) in a pediatric emergency department (PED) population.MethodsThis prospective, observational study was conducted from July 2017 to November 2017 at the PED of a free‐standing, inner‐city children's hospital. Patients 10 to 18 years of age presenting with chief complaints related to high‐risk social or sexual behaviors were recruited in a representative convenience sampling. A previously develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…The authors found that "no instrument had adequate levels of evidence for all criteria, and no criteria were met by all instruments" [64]. Our review also resulted in similar findings to the original review by Bailhache et al [13], in that 1) most studies did not report sufficient information to judge all criteria in the risk of bias tool; 2) most studies did not clearly blind the analysis of the reference standard from the index test (or the reverse); 3) some studies [26,36,37,39] included the index test as part of the reference standard (incorporation bias), which can overestimate the accuracy of the index test; and 4) some studies used a case-control design [29,31,36], which can overestimate the performance of the index test. A particular challenge, also noted by Bailhache et al [13], was the quality of reporting in many of the included studies.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The authors found that "no instrument had adequate levels of evidence for all criteria, and no criteria were met by all instruments" [64]. Our review also resulted in similar findings to the original review by Bailhache et al [13], in that 1) most studies did not report sufficient information to judge all criteria in the risk of bias tool; 2) most studies did not clearly blind the analysis of the reference standard from the index test (or the reverse); 3) some studies [26,36,37,39] included the index test as part of the reference standard (incorporation bias), which can overestimate the accuracy of the index test; and 4) some studies used a case-control design [29,31,36], which can overestimate the performance of the index test. A particular challenge, also noted by Bailhache et al [13], was the quality of reporting in many of the included studies.…”
Section: Discussionsupporting
confidence: 74%
“…1). From this set of results, 93 full-text articles were reviewed for inclusion, of which 19 new articles (representing 18 studies) were included [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. In addition, the 13 studies evaluated in the Bailhache et al review [43][44][45][46][47][48][49][50][51][52][53][54][55] were included in this review update, for a total of 32 articles (31 studies).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple healthcare institutions and organizations have developed trafficking screening tools, 9 , 10 yet only the Child Sex Trafficking Screening Tool is validated for healthcare settings and it is explicitly for sex trafficking screening of adolescents presenting with specific chief complaints. 11 The social, and, in some states, legislative pressure to identify trafficking has led institutions to use unvalidated trafficking screening tools. 12 , 13 Unvalidated tools lack sensitivity and specificity with the potential to negatively impact individual patient care and ultimately public health data collection.…”
Section: Introductionmentioning
confidence: 99%